Platelet-Released Growth Factors Induce Differentiation of Primary Keratinocytes. (20th July 2017) - Bayer, Andreas; Tohidnezhad, Mersedeh; Lammel, Justus; Lippross, Sebastian; Behrendt, Peter; Klüter, Tim; Pufe, Thomas; Jahr, Holger; Cremer, Jochen; Rademacher, Franziska; Gläser, Regine; Harder, Jürgen
Abstract : Autologous thrombocyte concentrate lysates, for example, platelet-released growth factors, (PRGFs) or their clinically related formulations (e.g., Vivostat PRF®) came recently into the physicians' focus as they revealed promising effects in regenerative and reparative medicine such as the support of healing of chronic wounds. To elucidate the underlying mechanisms, we analyzed the influence of PRGF and Vivostat PRF on human keratinocyte differentiation in vitro and on epidermal differentiation status of skin wounds in vivo. Therefore, we investigated the expression of early (keratin 1 and keratin 10) and late (transglutaminase-1 and involucrin) differentiation markers. PRGF treatment of primary human keratinocytes decreased keratin 1 and keratin 10 gene expression but induced involucrin and transglutaminase-1 gene expression in an epidermal growth factor receptor- (EGFR-) dependent manner. In concordance with these results, microscopic analyses revealed that PRGF-treated human keratinocytes displayed morphological features typical of keratinocytes undergoing terminal differentiation. In vivo treatment of artificial human wounds with Vivostat PRF revealed a significant induction of involucrin and transglutaminase-1 gene expression. Together, our results indicate that PRGF and Vivostat PRF induce terminal differentiation of primary human keratinocytes. This potential mechanism may contribute to the observed beneficial effects in the treatment of hard-to-heal wounds with autologous thrombocyte concentrate lysates in vivo .